1993
DOI: 10.1152/ajpheart.1993.264.4.h1208
|View full text |Cite
|
Sign up to set email alerts
|

ATP depletion causes a reversible decrease in Na+ pump density in cultured ventricular myocytes

Abstract: To examine factors contributing to impaired K+ homeostasis induced by prolonged but sublethal ATP depletion, we subjected cultured chick ventricular myocytes to metabolic inhibition with 20 mM 2-deoxy-D-glucose plus 1 mM NaCN for 2 h and then allowed myocytes to recover for 5 days in medium containing 6% fetal calf serum (FCS) or in hormone-supplemented serum-free medium. We measured spontaneous contractions (with a video motion detector), K+ content, K+ uptake, membrane potential, and Na+ pump density ([3H]ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…If it can be assumed that both ventral and dorsal cell types express primarily the á3 isoform and that they have identical pump stoichiometry and turnover rate, then the density of pump molecules apparently becomes an important factor affecting the amplitude of the pump current. The membrane density of the Na¤-K¤-ATPase varies widely among different cell types and even in a given cell the membrane distribution of pump molecules can be highly heterogenous (Allen et al 1989;Cramb et al 1989;McGrail et al 1991;Ikenouchi, Zhao, McMillan, Hammond & Barry, 1993;Wang et al 1993). An example of such functional differential distribution has been described recently in guinea-pig heart where the atrial and ventricular myocytes are reported to contain different amounts of pump molecules and, as a result, exhibited different contractile force in response to ouabain (Wang et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…If it can be assumed that both ventral and dorsal cell types express primarily the á3 isoform and that they have identical pump stoichiometry and turnover rate, then the density of pump molecules apparently becomes an important factor affecting the amplitude of the pump current. The membrane density of the Na¤-K¤-ATPase varies widely among different cell types and even in a given cell the membrane distribution of pump molecules can be highly heterogenous (Allen et al 1989;Cramb et al 1989;McGrail et al 1991;Ikenouchi, Zhao, McMillan, Hammond & Barry, 1993;Wang et al 1993). An example of such functional differential distribution has been described recently in guinea-pig heart where the atrial and ventricular myocytes are reported to contain different amounts of pump molecules and, as a result, exhibited different contractile force in response to ouabain (Wang et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In this context we describe relevant results using giant excised cardiac patches to analyze Na/K pump currents. Additionally, it is suggested that Na/K pumps become inhibited during ATP depletion by mechanisms that are not simply related to substrate binding 32,44,45 . A still more complex scenario is suggested by evidence that phosphorylation of phospholemman, which is thought to regulate cardiac pumps, has a strong stimulatory effect on Na/K pumps that opposes effects of the pump inhibitor induced by ischemia 46 …”
Section: Introductionmentioning
confidence: 99%
“…Increased intracellular Na ϩ is suggested as a major cause of NCX to run in Ca 2ϩ influx mode and causes Ca 2ϩ accumulation in the cardiomyocytes during reperfusion. The possible mechanisms for the increase in intracellular Na ϩ during ischemia (53) are decreased Na ϩ -K ϩ -ATPase activity (1,17,18,29,32), tissue acidosis, and increased tissue CO 2 (8,49) with increased Na ϩ /H ϩ exchange activity (1,20,23,24,33,54) and Na ϩ entry via Na ϩ channels and possibly other cation channels. The markedly larger inhibitory effect of ranolazine, the inhibitor of late Na ϩ current (50), on the increase in exchangeable Ca 2ϩ and the increase in LD release in sham cells than in CHF cells after reoxygenation indicates that differences between CHF and sham cells in late Na ϩ current during hypoxia might explain the differences in Na ϩ uptake during hypoxia and the differences in ischemia tolerance observed in this study.…”
Section: Discussionmentioning
confidence: 99%